Look to the field. (10th February 2022) - Iliev, Rumen; Medin, Douglas; Bang, Megan
Abstract: Yarkoni's paper makes an important contribution to psychological research by its insightful analysis of generalizability. We suggest, however, that broadening research practices to include field research and the correlated use of both converging and complementary observations gives reason for optimism.